TRANSISI GREEN FINANCE KE SUSTAINABLE FINANCE: TINJAUAN SISTEMATIS ATAS STANDAR PELAPORAN AKUNTANSI DAN PENGUKURAN ESG - Fiesty Utami; Refi Pratiwi; Tri Wahyudi (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2026)
The transition from green finance to sustainable finance is the transformation of the financial system and the way the market takes environmental, social, and governance factors into decision-making. Although accounting standards and sustainability reporting frameworks have evolved rapidly, there is still substantial fragmentation between global markets regarding definitions, measurement approaches, and implementation practices. We conducted a systematic review following the PRISMA guidelines to investigate this topic. Five structured keyword combinations on sustainable finance, ESG integration, and reporting standards were used to search five academic databases for published articles. Of the 1038 records identified, 895 were eligible for title screening and duplicate abstracts were removed. Of these, 807 articles were reviewed full text for feasibility as shown in the PRISMA flow process. In the end, 121 studies were obtained that qualified the sustainable finance transition, accounting methods and reporting frameworks and corporate disclosure practices. The collected studies are divided by type of research: bibliometric studies, empirical analysis, systematic literature reviews and other methodological designs. The key reporting frameworks identified include: SASB, GRI, ISSB, TCFD, and EU CSRD. This review found a small to moderate positive association between company performance and ESG integration, but the certainty of the evidence was low. While the literature suggests the role of green finance in supporting environmental projects, these findings are still inconclusive due to the lack and heterogeneity of evidence.